2016
DOI: 10.1088/0031-9155/61/11/4061
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid x-space: a new approach for MPI reconstruction

Abstract: Magnetic particle imaging (MPI) is a new medical imaging technique capable of recovering the distribution of superparamagnetic particles from their measured induced signals. In literature there are two main MPI reconstruction techniques: measurement-based (MB) and x-space (XS). The MB method is expensive because it requires a long calibration procedure as well as a reconstruction phase that can be numerically costly. On the other side, the XS method is simpler than MB but the exact knowledge of the field free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…First, the reconstruction module integrates the classical system matrix‐based and the x‐space reconstruction methods. More advanced reconstruction methods, such as the sparse system matrix reconstruction 23 and the hybrid x‐space reconstruction methods 19 can be integrated into MPIRF. Second, the main parameters of the MPI scanner were used in MPIRF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the reconstruction module integrates the classical system matrix‐based and the x‐space reconstruction methods. More advanced reconstruction methods, such as the sparse system matrix reconstruction 23 and the hybrid x‐space reconstruction methods 19 can be integrated into MPIRF. Second, the main parameters of the MPI scanner were used in MPIRF.…”
Section: Discussionmentioning
confidence: 99%
“…14 Many MPI image-reconstruction methods have been reported in the past decade; they can be mainly divided into system matrix-based 15,16 and x-space methods. [17][18][19] The reconstruction framework integrates the reconstruction methods, reduces the negative computer computing power of new reconstruction methods, and simplifies the deployment of the new method in the application environment, thereby reducing the application complexity of the new method, accelerating new method development, and promoting MPI development in clinical applications. However, there is no unified software framework for integrating the two MPI image reconstruction methods.…”
mentioning
confidence: 99%
“…Pre-clinical system Please do not adjust margins Please do not adjust margins specifications are slowly improving as researchers have been highly active in designing improved software for image acquisition and reconstruction. 35,37,39,40,[365][366][367][368][369][370][371][372][373] For example, Gladiss et al recently demonstrated the advantages of a hybrid system matrix for efficient calibration and image reconstruction. 374 To scale-up MPI hardware to human-size, there are several notable safety considerations and ergonomic challenges that must be overcome.…”
Section: Clinical Translationmentioning
confidence: 99%
“…On the other hand, XS works only for uniformly spatial drive fields. In recent years, a different Hybrid XS (HXS) approach, combining both the MB and XS, was also proposed in [55,56]. An interesting overview of all methods techniques adopted in MPI, together with their preclinical investigations, can be found in [33].…”
Section: Magnetic Particle Imagingmentioning
confidence: 99%
“…The parameter values used in the corresponding numerical algorithms are listed in Table 1 (Step 2). The resulting images u x and u y was firstly processed by a Wiener's deconvolution (Step 3) and successively merged pixel by pixel into the final image u by a geometrical mean, that is u(i, j) = u x (i, j)u y (i, j), as done in [56] (Step 4). At this last step a further processing by a high-pass filter was performed.…”
Section: Application Of Pdes Inpainting To Mpimentioning
confidence: 99%